The analysis of teachers’ professional competence in utilizing information and communication technology - Abkarin, Noven Aquilla (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
This study is about the utilization of ICT in classroom learning to develop teacher’s professional competence. Nowadays, COVID-19 pandemic has already spread around the world. It brings bad impacts on many sectors, especially the education sector. Based on the issue, this study aims to investigate teacher’s familiarity with the use of ICT, to find out teachers’ professional competence in utilizing ICT in classroom learning, and to obtain supporting and inhibiting factors of teachers’ professional competence in utilizing ICT. A qualitative approach was used as a method of this study. Data collection was conducted by distributing questionnaires, carrying out structured interviews, and documentation addressed to ten respondents consisting of English teachers from three schools in Wonosobo, Central Java, Indonesia. This study reveals that ten teachers were familiar with using ICT in classroom learning. They claimed that the use of ICT can help their works in the teaching and learning process. Second, the teacher’s professional competence can improve ICT utilization in teaching and learning classrooms. The use of ICT also can improve teachers’ professional competence because ICT usage is easier and more effective to deliver materials. Third, some supporting factors of the use of ICT were found in this study. They were making teaching and learning process easier, increasing students’ motivation, and improving teachers’ professional competence. The use of ICT also could make teachers easily take part in this digital era.